A study on E- Promotional strategies for e-marketing - Ms.K.Priyadarsini, Dr.S.Shanthakumari, (International Journal of Scientific Research and Management (IJSRM), 2017)
The key to greater promotional impact for retailers and manufacturers today is knowledge and insight. Inorder to maximize promotional effectiveness, organizations need to know what categories and what brandsare being promoted, by whom, at what price points and how often they are changing. Since online Web sitepromotions will only continue to grow; successful businesses need to be strategic and informed in theirapproach.To help retailers and manufacturers successfully implement strategically aligned online and offlinepromotions. So, this study focuses on e-promotional strategies needed for effective e-marketing